2014
DOI: 10.1099/ijs.0.056721-0
|View full text |Cite
|
Sign up to set email alerts
|

Chitinophaga jiangningensis sp. nov., a mineral-weathering bacterium

Abstract: A Gram-stain-negative, rod-shaped bacterial strain, JN53 T , was isolated from the surfaces of weathered rock (potassic trachyte) from Nanjing, Jiangsu Province, PR China. Strain JN53 T grew optimally at 30 6C, pH 7.0. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain JN53 T belonged to the genus Chitinophaga in the family Chitinophagaceae. It was most closely related to Chitinophaga terrae KP01 T (97.3 % 16S rRNA gene sequence similarity), Chitinophaga eiseniae YC6729 T (96.3 %). St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…The tested bacterium, C. jiangningensis JN53, is a novel mineral‐weathering bacterium isolated from weathered rock surfaces . C. jiangningensis JN53 was able to weather rock (potassic trachyte).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tested bacterium, C. jiangningensis JN53, is a novel mineral‐weathering bacterium isolated from weathered rock surfaces . C. jiangningensis JN53 was able to weather rock (potassic trachyte).…”
Section: Methodsmentioning
confidence: 99%
“…C. jiangningensis JN53 was able to weather rock (potassic trachyte). Rock dissolution experiments showed that Fe, Al, Si, and K releases by C. jiangningensis JN53 from the rock were increased by 5.8‐fold, 144‐fold, 18%, and 34%, respectively, compared to the uninoculated controls . The liquid nutrition‐rich sucrose‐minimal salts K‐limited medium (SSKM) (1.0% sucrose, 0.1% (NH 4 ) 2 SO 4 , 0.2% Na 2 HPO 4 , 0.05% MgSO 4 , 0.01% NaCl), nutrition‐moderate Bushnell‐Haas medium (BHm) (0.002% KCl, 0.015% MgSO 4 · 7H 2 O, 0.008% NaH 2 PO 4 · 2H 2 O, 0.009% Na 2 HPO 4 · 2H 2 O, 0.0065% (NH 4 ) 2 SO 4 , 0.01% KNO 3 , 0.002% CaCl 2 , and 0.2% glucose) , and nutrition‐poor BHm (BHm without KCl and KNO 3 ) were used to evaluate the mineral weathering behaviors of C. jiangningensis JN53.…”
Section: Methodsmentioning
confidence: 99%
“…Cells of members of the genus Chitinophaga are Gram-stain-negative, non-motile or motile by sliding, non-spore-forming rods and are oxidase-variable (Kämpfer et al , 2006; Chung et al , 2012). At the time of writing, the genus Chitinophaga comprises 19 species with validly published names, including five recently described species, Chitinophaga cymbidii (Li et al , 2013), Chitinophaga jiangningensis (Wang et al , 2014), Chitinophaga polysaccharea (Han et al , 2014), Chitinophaga taiwanensis (Lin et al , 2014) and Chitinophaga costaii (Proença et al , 2014). In this study, polyphasic characterization of a mineral-weathering bacterium (strain JN246 T ) was performed.…”
mentioning
confidence: 99%
“…Kämpfer et al (2006) reclassified four species, [Flexibacter] sancti , [ Flexibacter ] filiformis , [ Flexibacter ] japonensis and [ Cytophaga ] arvensicola , to the genus Chitinophaga and described a novel species, Chitinophaga skermanii . Species of the genus Chitinophaga have mostly been isolated from roots of different plants such as Arabidopsis thaliana (Lin et al , 2014) and Cymbidium goeringii (Li et al , 2013), rhizosphere soils and weathered rocks (Wang et al , 2014). Cells of members of the genus are Gram-negative, non-motile, non-spore-forming and rod-shaped.…”
mentioning
confidence: 99%
“…Cells of members of the genus are Gram-negative, non-motile, non-spore-forming and rod-shaped. At the time of writing, there are 19 species with validly published names in the genus Chitinophaga , including the recently described Chitinophaga jiangningensis (Wang et al , 2014), Chitinophaga polysaccharea (Han et al , 2014), Chitinophaga taiwanensis (Lin et al , 2014) and Chitinophaga costaii (Proença et al , 2014).…”
mentioning
confidence: 99%